On the growth of anhydrous Mg-bearing carbonates – Implications from norsethite growth kinetics. (1st October 2018) - Lindner, Michael; Saldi, Giuseppe D.; Carrocci, Salvatore; Bénézeth, Pascale; Schott, Jacques; Jordan, Guntram
Abstract: At ambient conditions, both dolomite [CaMg(CO3 )2 ] and magnesite [MgCO3 ] do not readily grow from aqueous solution. A common explanation for this is the highly hydrated character of Mg 2+ . The exceptionally easy growth of norsethite [BaMg(CO3 )2 ], however, clearly shows that Mg 2+ ions, in principle, can rapidly dehydrate and incorporate into anhydrous carbonate minerals even at ambient conditions. Still, the lack of reliable quantitative data prevents the necessary comparison of the reactivities of these magnesium-bearing minerals. In order to shed light on the span of possible incorporation rates of anhydrous Mg 2+ ions, we present the first systematic quantitative study of norsethite growth kinetics as well as the determination of norsethite solubility product over a wide range of temperatures to replace the diffuse qualitative knowledge existing so far. Norsethite solubility was determined in 0.1 M NaCl aqueous solutions from 30 to 150 °C using a hydrogen-electrode concentration cell, which provides a continuous in-situ measurement of hydrogen ion molality. The solubility product of norsethite can be described by log10 K sp°-nrs = a + b / T + cT, where a = 31.007, b = −7321.122, and c = −0.0811. Gibbs free energy ( Δ f G 298.15 0 ) and enthalpy ( Δ f H 298.15 0 ) of norsethite formation were determined to be −2167 ± 2 kJ/mol and −2351 ± 2 kJ/mol, respectively. Growth experiments were conducted in mixed-flow reactors covering a significant span of solution compositions (pH: 7.0–8.5, [Ba]: 3 × 10 −6 –5 × 10 −3 M, [Mg]: 1 × 10 −4 –9 × 10 −2 M, ionic strength: 0.1 M, Ωnorsethite = 1–290) and temperatures (40, 65, and 100 °C). From the experimental data, the apparent activation energy of norsethite growth rate constant was determined to be Ea = 80 ± 7 kJ/mol. An extrapolation to 25 °C resulted in a rate constant of k nrs 25 ∘ C = 1.8 × 10 −2 nmol m −2 s −1 with a reaction order of 1.2 ± 0.1. These results allowed for a direct, quantitative comparison of the growth rates of different anhydrous Mg-bearing carbonate minerals. This comparison revealed that the growth rate constant of norsethite at 100 °C is approximately three orders of magnitude higher than that of magnesite and five orders of magnitude higher than that of dolomite. In the case of norsethite, obviously some effective means must exist which promotes the dehydration of the Mg ion and allows for the rapid incorporation of dehydrated Mg 2+ into the growing mineral. This promotion has to take place at the norsethite surface where the hydration energy of Mg 2+ can significantly differ from the well-known value in bulk solution. Consequently, not only the stability of the aqueous metal complex per se is an important factor controlling the growth rate of anhydrous magnesium bearing carbonate minerals but also the means of a given surface to weaken the stability of this complex.